The Effectiveness of Geospatial Technology-Integrated Project-Based Learning Model on Students' Spatial Thinking Skills Across Different Learning Styles - Adipranata, Zahrofi; Fitriana, Evi; Deffinika, Ifan (ASANKA : Journal of Social Science and Education, 2026)
Spatial thinking is essential in geography learning for understanding human-space relationships, yet conventional instruction often fails to develop higher-order spatial reasoning. This study examines the effectiveness of a geospatially integrated Project-Based Learning (PjBL) model on students’ spatial thinking skills, while accounting for learning styles as a moderating variable. A quasi-experimental pretest-posttest control-group design was employed, involving 425 tenth-grade students from SMAN 1 Batu. Two purposively selected classes served as the experimental (geospatial PjBL using Google Earth) and control (lecture-based instruction) groups. Results showed that the geospatially integrated PjBL model significantly improved students' spatial thinking abilities (p < 0.001). The most substantial improvement occurred in the Tools of Representation dimension, followed by the Concepts of Space and the Cognitive Processes to Evaluate Spatiality dimensions. Moreover, students with kinesthetic and audio-visual learning styles showed greater improvement than those with purely auditory or visual preferences. These findings suggest that integrating geospatial technology into PjBL strengthens spatial visualization and cognitive processes through active, contextual experiences. This study contributes by integrating learning styles as a moderating variable into geospatial PjBL, an underexplored area.